Effects of acceptance and commitment therapy on cognitive function: a systematic review - Liu, Haihong; Liu, Nan; Chong, Sheau Tsuey; Boon Yau, Eugene Koh; Ahmad Badayai, Abdul Rahman (Elsevier, 2023)
Cognitive function is essential for daily activities. Acceptance and commitment therapy (ACT) may improve cognitive function by enhancing psychological flexibility, but the underlying mechanism is unknown. This systematic review evaluated the effectiveness of ACT on cognitive function. Seven research databases (PubMed, ProQuest Dissertations and Theses, Web of Science, EBSCOhost, CNKI, Scopus, Wanfang) were searched to collect articles with trials published in English and Chinese. After applying inclusion and exclusion criteria, we identified 12 studies published between 1994 and 2022 that included a combined total of 904 participants. Among the included studies were within-group (N = 3) and randomized controlled trial (RCT, N = 9) study designs. Outcome measures included cognitive scales and behavioral measurements. Of the 12 articles, 10 studies showed improvements in certain domains of cognitive function due indirectly to ACT intervention. We found that the ability of ACT intervention to promote psychological flexibility is due to its transdiagnostic nature. Also, the effects of the ACT intervention were observed in multiple cognitive domains: attention, subjective cognitive function, executive function, and memory. In conclusion, cognitive trainers could consider practicing ACT as part of their strategy to enhance an individuals psychological flexibility and cognitive function.